Neutrophile-Lymphocyte Ratio and Outcome in Takotsubo Syndrome - David Zweiker; Edita Pogran; Laura Gargiulo; Ahmed Abd El-Razek; Ivan Lechner; Ivan Vosko; Stefan Rechberger; Heiko Bugger; Günter Christ; Diana Bonderman; Evelyn Kunschitz; Clara Czedik-Eysenberg; et al. (Biology, 2022)
Background: Takotsubo syndrome (TTS) is an important type of acute heart failure with significant risk of acute complications and death. In this analysis we sought to identify predictors for in-hospital clinical outcome in TTS patients and present long-term outcomes. Methods: In this analysis from the Austrian national TTS registry, univariable and multivariable analyses were performed to identify significant predictors for severe in-hospital complications requiring immediate invasive treatment or leading to irreversible damage, such as cardiogenic shock, intubation, stroke, arrhythmias and death. Furthermore, the influence of independent predictors on long-term survival was evaluated. Results: A total of 338 patients (median age 72 years, 86.9% female) from six centers were included. Severe in-hospital complications occurred in 14.5% of patients. In multivariable analysis, high neutrophile-lymphocyte-ratio (NLR; OR 1.04 [95% CI 1.02–1.07], p = 0.009) and low LVEF (OR 0.92 [0.90–0.95] per %, p < 0.001) were significant predictors of severe in-hospital complications. Both the highest NLR tercile and the lowest LVEF tercile were significantly associated with reduced 5-year survival. Conclusions: Low LVEF and high NLR at admission were independently associated with increased in-hospital complications and reduced long-term survival in TTS patients. NLR is a new easy-to-measure tool to predict worse short- and long-term outcome after TTS.